Media Literacy Based On Environmental Factors: A Case Study In Palembang City - Murti, Krisna; Meilinda, Nurly; Farodiyah, Nanda Narul; Mahdavikia, Reza; Musdalifah, Farisha Sestri (KOMUNIKA, 2024)
This study examines the integrated role of educational institutions, media, and government in promoting media literacy among Palembang City residents using the Environmental Factors concept from the European Commission. The research employs a qualitative case study approach through in-depth interviews with key stakeholders, including educators, lecturers, Regional Indonesian Broadcasting Commission representatives, journalists, and media activists. The study reveals that successful media literacy promotion requires collaborative efforts between government agencies, educational institutions, and media organizations. The findings indicate that media availability in Palembang includes diverse internet providers, widespread smartphone penetration, and multiple radio and television stations. However, the media literacy context shows gaps in formal education integration, limited policy frameworks, and insufficient civil society participation. The research demonstrates that the synergy between government initiatives, educational programs, and media industry participation significantly enhances media literacy skills among citizens. These findings contribute to understanding multi-stakeholder approaches in media literacy education and provide practical insights for developing comprehensive media literacy strategies in urban Indonesian contexts.